(untitled) (The Geographic Base, 2024)
Identification and classification of soil texture is one of the most important components of crop production, agricultural sustainability and land use management. Kavrepalanchok district plays an important role in potato production in Nepal. Therefore, this study was conducted to know the state of potato production, particularly, the relationship between soil pH, textural class, and soil productivity status with potato production in Ward No. 3 of Banepa Municipality of Kavrepalanchok District. Thirty-five sample plots were collected from the different locations in the study area. Questionnaire survey was conducted for the same households representing each sample plot and three key informant interviews with elderly farmers were undertaken for the information of history and types of potato used in farming. Soil samples were tested and analyzed at the soil laboratory of the Central Department of Geography, Tribhuvan University. The results show that the soil texture consisted of sandy loam, sandy clay loam, loam, loamy sand, and silty loam. Soil pH ranged from strongly acidic to moderately alkaline, and the mean productivity of potato was found at 1.41 kg per m2. For soil textural management, farmers used chemical fertilizers such as urea, DAP, and potash, while also employing animal manure, poultry manure, and green manure as organic fertilizers. The farmers used pesticides in the potato farms to control blight, apply micronutrients, and kill pests (insects, weeds). To treat other illnesses and weeds in potatoes, the majority of the farmers utilized herbicides in the highland or upper sloppy terrace fields (Baari land), but not in the lowland fields (Khet land). The improved variety of potato seeds available from government offices and cooperatives is found to be used by a few commercialized farmers.